0744 Risk Factors for PAP Adherence in Children with Sleep Apnea: Results Derived Using a Big Data Approach. (12th April 2019) - Bhattacharjee, Rakesh; Benjafield, Adam; Armitstead, Jeff; Cistulli, Peter; Nunez, Carlos; Pepin, Jean-Louis; Woehrle, Holger; Yan, Yang; Malhotra, Atul
Abstract: Introduction: Pediatric Obstructive Sleep Apnea (POSA), affects up to 10% of children. Adenotonsillectomy, the recommended therapy for POSA, is modestly effective in adolescents and obese children. Subsequently, children are often prescribed positive airway pressure (PAP) therapy. Published studies of small cohorts have identified risk factors associated with pediatric PAP non-adherence. Using a Big Data approach, we assessed "real-world" PAP adherence in children, and evaluated specific predictive factors associated with adherence. Methods: Analysis of the AirView database (ResMed Corp) from October 1 st 2014 to August 1 st 2018 was conducted. AirView stores data derived from active PAP devices on a nightly basis to the cloud to help providers remotely monitor adherence. Data collected includes nightly PAP usage (total duration), efficacy of PAP including residual apnea hypopnea index (rAHI), and mask leak (L/min). US patients with an age <18 and > 4 years at time of device activation were included. Children using only continuous PAP (CPAP) and auto-titrating PAP (APAP) were evaluated. Children using noninvasive ventilation were excluded. CMS adherence criteria were used. The study was reviewed by an institutional review board (IRB) and deemed exempt from IRB oversight. Results: PAP device data were available from 20, 533 children. Overall mean reported adherence in children was 45.1±33.3% (mean±SD) of days of usage for ≥4 hours with 9504 (46.3 %) children meeting CMS adherence criteria after 90 days. Mean nightly hourly usage was 3.9±2.8h. A rAHI < 5 events (p<0.001), 95 th percentile pressure ≥ 8cmH2O (p<0.001), median leak < 12 L/min (p<0.001) were all significantly associated with a higher likelihood of longer term adherence. Conclusion: This analysis from the AirView database represents the largest analysis of children using PAP therapy. Our study shows room for improvement with PAP adherence and confirms several predictive factors associated with improved adherence in children. Several modifiable factors such as mask leak could be addressed to optimize adherence. Additional analysis will include the effect of age and early monitoring of AirView on long-term adherence. Support (If Any): This study was supported by ResMed.